PERSPEKTIF MUHAMMAD ‘ABDUH DALAM PEMBAHARUAN PENDIDIKAN ISLAM - Yogi Fernando; Nunu Burhanuddin (CV. ADIBA AISHA AMIRA, 2023)
The science of education always develops with the times. Therefore, the education system must be changed. Describing the results of the study, the researcher offers Muhammad